2013
DOI: 10.1002/ajmg.a.35884
|View full text |Cite
|
Sign up to set email alerts
|

Multiple neurofibromas as the presenting feature of familial atypical multiple malignant melanoma (FAMMM) syndrome

Abstract: Mutations in the cyclin-dependent kinase inhibitor-2A (CDKN2A) gene have been associated with a number of malignancies, most notably cutaneous malignant melanoma (CMM). Mutations in this gene have also been associated with pancreatic cancer and breast cancer, as well as astrocytomas and other nervous system tumors (NST). Among NST, rare solitary internal neurofibromas have been reported, but multiple cutaneous neurofibromas have only been described in two families. In the first family, the affected individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…However, in their study, they also identified a new long non-coding RNA, within the germline deletion, which they called ANRIL (Antisense Noncoding RNA in the INK4A Locus). More recently, Vanneste et al 34 reported a patient with multiple neurofibromas and a solitary spinal neurofibroma who was found to have a deletion of 14 nucleotides in exon 2 of CDKN2A, providing further evidence that p14 ARF , p16 INK4A and/or ANRIL , now designated CDKN2B-AS1, may be specifically involved in the aetiology of neurofibromas as a feature of FAMMM. However, numerous FCMM families with large deletions impacting p14 ARF do not have neural system tumours3 35 [Goldstein et al unpublished data 2015].…”
Section: Discussionmentioning
confidence: 98%
“…However, in their study, they also identified a new long non-coding RNA, within the germline deletion, which they called ANRIL (Antisense Noncoding RNA in the INK4A Locus). More recently, Vanneste et al 34 reported a patient with multiple neurofibromas and a solitary spinal neurofibroma who was found to have a deletion of 14 nucleotides in exon 2 of CDKN2A, providing further evidence that p14 ARF , p16 INK4A and/or ANRIL , now designated CDKN2B-AS1, may be specifically involved in the aetiology of neurofibromas as a feature of FAMMM. However, numerous FCMM families with large deletions impacting p14 ARF do not have neural system tumours3 35 [Goldstein et al unpublished data 2015].…”
Section: Discussionmentioning
confidence: 98%
“…These findings raised the question whether the genes involved in these biallelic losses are tumor suppressor genes and therefore crucial for tumor progression. The deleted region at 9p21 of a size 4 Mb is already known to have the tumor recessive gene CDKN2A , which codes for two tumor suppressor genes, p14 and p16, and has been associated with development of malignant melanoma, pancreatic cancer, breast cancer, astrocytomas and nervous system tumors . Deletion of 9p21 has been seen in 17% of benign, 52% of atypical, and 74% of anaplastic meningiomas and has been considered to be associated with malignant progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The deleted region at 9p21 of a size 4 Mb is already known to have the tumor recessive gene CDKN2A, which codes for two tumor suppressor genes, p14 and p16, and has been associated with development of malignant melanoma, pancreatic cancer, breast cancer, astrocytomas and nervous system tumors. 32 Deletion of 9p21 has been seen in 17% of benign, 52% of atypical, and 74% of anaplastic meningiomas and has been considered to be associated with malignant progression and poor prognosis. The overall survival rates at 1, 2 and 3 years for patients with anaplastic meningiomas with no.…”
Section: Discussionmentioning
confidence: 99%
“…Due to alternative splicing, several long, short and circular isoforms of ANRIL exist [91]. ANRIL expression has been linked to several conditions, including the risk of melanoma [92,93]. …”
Section: Long Non-coding Rnas In Melanomamentioning
confidence: 99%